Exploring the Evolution of Network Architectures: From Traditional Systems to Future Innovations - Raja, L V (Journal of Neonatal Surgery, 2025)
The advance of network topologies has been a technological constant that laid the foundation for industries a societies’ digitalisation. The conventional network systems that are the basis of computing have however been found wanting in terms of scale, elasticity, and dynamism to meet new demands. The following paper aims to identify the trends of network architecture development with reference to the transition from the current centralised architectures to Software Defined Networking, Network Function Virtualization, and Edge Computing. The accelerating trends that are characterized are the increasing number of connected devices, increasing application-data intensity and the requirement of low latency. Despite these innovations these have served to overcome many of the problems associated with the traditional architectures but at the same time, they have posed problems like complexity, insecurity and interoperability among the many technologies involved. These questions and options are the subject of this paper, which focuses on AI, ML, and blockchain in their capacity as the keys to the networks of the future. In that spirit, this research has sought to offer an outline of the present and future trend as a way of helping the interested parties make sense of issues as they are, and as they are likely to develop in the future